Terapi Sistemik Defisit JKN: Bahan Refleksi Bagi Semua Pihak - Hidayat, Budi (UI Scholars Hub, 2016)
The deficit deserves to be considered a chronic JKN disease. Indications of the deficit are revealed from the claims ratio figures. In 2014 and 2015, the claims ratio was consistently above 100%. This figure results from dividing claim costs (or participant health costs) by contribution income. Thus, the claims ratio describes the absorption of contribution funds for health costs only. However, contribution income must also be allocated for operational expenses and reserves. The JKN deficit will continue to grow if systemic therapy is nil. For 2016, the author's estimation results by referring to the assumed contribution amounts by Presidential Regulation No. 28/2016 (Cabinet Secretariat, 2016) and service rates in Minister of Health Regulation 59/2014 (Minister of Law and Human Rights, 2014) found a claim ratio of 101%. This means that contribution income still needs to be increased, even if only to fund health services. Where do the funds come from to fund operational costs? Does JKN only rely on government funding injections? The label of chronic deficit disease deserves to be carried by JKN. What is the cure?